2009
DOI: 10.1016/j.crci.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Green chemistry approaches for the synthesis of quinoxaline derivatives: Comparison of ethanol and water in the presence of the reusable catalyst cellulose sulfuric acid

Abstract: Quinoxaline derivatives have been synthesized in high yields in the presence of cellulose sulfuric acid as an inexpensive, recyclable and biodegradable solid acid catalyst in H 2 O or EtOH at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…, in the synthesis of quinoxaline from o-phenylenediamine and benzyl is compared with the efficiencies of two solid acid catalysts cellulose sulfuric acid (CSA) and silica sulfuric acid (SSA) reported for the same reaction [21,22]. Table 4 gives the product yield in EtOH and H 2 O for each catalyst and its reusability in EtOH.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…, in the synthesis of quinoxaline from o-phenylenediamine and benzyl is compared with the efficiencies of two solid acid catalysts cellulose sulfuric acid (CSA) and silica sulfuric acid (SSA) reported for the same reaction [21,22]. Table 4 gives the product yield in EtOH and H 2 O for each catalyst and its reusability in EtOH.…”
Section: àmentioning
confidence: 99%
“…But this catalyst is acidic, hygroscopic and hazardous in nature. Ahmad shaabani et al [21,22] reported two solid acid catalyst cellulose sulfuric acid (CSA) and silica sulfuric acid (SSA) for this synthesis. Though they give good yield with reusability, preparation of these catalysts involves the evolution of HCl.…”
Section: Introductionmentioning
confidence: 98%
“…Uma das áreas com maior destaque nessas pesquisas foi, e ainda é, a de catálise, cujo objetivo é a maximização das reações e redução da formação de subprodutos indesejáveis durante o processo. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Isso pode ser, obviamente, atribuído a algumas características importantes dos catalisadores e sua importância econô-mica. Em geral, as sínteses catalíticas, devido à elevada seletividade, são mais eficientes, limpas e econômicas, permitem a reutilização do catalisador, o uso de matérias-primas renováveis ou a redução de reagentes, sendo superiores aos reagentes estequiométricos.…”
Section: A Temática Química Verde Nos Periódicos Científicosunclassified
“…have been reported the synthesis of quinoxaline derivatives using gallium(III) triflate in good yield, less reaction time but catalyst has some disadvantages like acidic, hygroscopic and hazardous in nature. Ahmad et al ,. reported two solid acid catalyst based on cellulose sulfuric acid and silica sulfuric acid for quinoxaline derivatives.…”
Section: Introductionmentioning
confidence: 99%